Dengue fever with encephalitis: a rare phenomenon. (15th June 2018) - Baheti, Gaurav; Mehta, Varshil; Ramchandani, Menka; Ghosh, Gopal Chandra
Abstract : The clinical profile and presentation of patients with dengue fever may differ from asymptomatic infection to the dreadful complications like dengue shock syndrome. However, neurological complications are very rare. Dengue encephalitis occurs by a direct involvement of central nervous system by the dengue virus which is an extremely rare complication. A 33-year-old man presented with fever, vomiting and severe headache. He had one episode of generalised tonic-clonic seizure followed by an altered sensorium on the day of admission to the hospital. The diagnosis of dengue fever was confirmed by dengue serology (IgM) and (NS1) antigen assay. MRI brain was suggestive of encephalitis. Thus, the patient was treated symptomatically and discharged in stable condition with minimal neurological deficit.